Documentación de los Procesos de Compra de Cacao, Para el Incremento de la Productividad en "Industrial Cacotera del Huila S.A. Tolimax S.A." - Calidad en las Compras de Cacao (2020)
The constant changes that exist in the business, industrial and commercial field, require that productive companies have to adapt to these changes in trends and tastes demanded by the market, which go hand in hand with globalization and economic tightening, in order to attract new customers and retain current ones, they see the obligation and need to develop and implement new market strategies and models for the optimization and standardization of production processes, giving rise to the productivity, efficiency and performance of material resources , technological and human, as the study of documentation of the cocoa purchase processes was carried out in the company Industrial Cacaotera del Huila SA- Tolimax SA In Tolimax SA, the production and commercialization of table chocolate based on cocoa almonds and complementary is carried out, for the food sector, to achieve the elaboration of this product, the necessary quantities and raw material have been identified, in each one of the process stages, in order to guarantee the quality of the product and the satisfaction of needs and expectations of customers and consumers. The production process is certified under the international standard ISO 9001: 2015 by the Colombian Institute of Technical Standards and Certification - ICONTEC International, since June 2018, the scope of the Quality Management System is the production of table chocolate; Similarly, it is also endorsed as a low-risk food under the health notification NSA-004256-2017 and NSA-00425-2017 whose validity expires on January 20, 2028, issued by the National Institute of Food and Drug Surveillance INVIMA. By diagnosing the documentation of the current cocoa purchase processes, the benefits and penalties for the current cocoa producer, it is possible to identify variables that help and coincide to make cocoa purchases more productive and efficient. In view of the company's wishes to internationalize and export table chocolate and other cocoa-almond-based products to Europe and the United States, as a proposal for the documentation of the cocoa purchase process, Tolimax will benefit since It will help you standardize these processes and avoid rework and improve productivity.